Frequencies of localized acoustic modes in dependence on mutual relation of components of Au/V nanolayers - Aleksiejuk, Mikołaj (Archives of Acoustics, 2007)
The paper presents the study of frequencies of the acoustic localized modes in metallic Au/V nanolayers. On the basis of Rytov model describing acoustic wave propagation in periodic layered medium and Djafari–Rouhani formula the frequencies of localized modes were numerically calculated. Dependencies of localized modes frequencies were presented graphically as a function of b/L nanolayer parameter (b – thickness of Au sublayer, L – thickness of Au/V bilayer) for first and second phononic stop bands. Obtained experimentally frequencies of localized modes for Au/V nanolayers were compared with calculated values. Accordance between experimental and theoretical results is satisfactory.